Changes in stress and recovery after heavy training in rowers - Jürimäe, J.; Mäestu, J.; Purge, P.; Jürimäe, T. (Journal of Science and Medicine in Sport, 2004)
In this study, the effect of rapidly increased training volume on performance, recovery-stress state and stress hormones over a six-day training camp were investigated in competitive male rowers (n=21). The training regimen consisted mainly of low-intensity on-water rowing and resistance training, in total 19.6+/-3.8 hrs, corresponding to approximately 100% increase in training load. Two thousand metre rowing ergometer performance time worsened by the end of a heavy training period. The resting blood testosterone decreased and cortisol remained unchanged. The Recovery-Stress-Questionnaire for Athletes (RESTQ-Sport) revealed an increase in somatic components of stress (Fatigue, Somatic Complaints, Fitness/Injury) and a decrease in recovery factors (Success, Social Relaxation, Sleep Quality, Being in Shape, Self-Efficacy). Relationships were observed between training volume, and Fatigue (r=0.49), Somatic Complaints (r=0.50) and Sleep Quality (r=-0.58) at the end of heavy training. In addition, relationships were also observed between cortisol and Fatigue (r=0.48) at the end of heavy training as well as between changes in cortisol and changes in Fatigue (r=0.57) and Social Stress (r=0.51). In conclusion, changes in specific stress and recovery scales of the RESTQ-Sport for athletes and changes in stress hormone values indicated a state of heavy training stress and incomplete recovery at the end of a six-day heavy training period.